Location and the multinational enterprise - Cantwell, John (Journal of International Business Studies, 2009)
In the early development of the international business field, the focus of attention moved from the country level to the firm level, and interest in location issues declined. More recently, firm-based research has itself become increasingly concerned with the study of firm–location interactions. When examining two-way knowledge flows or spillovers between multinational enterprises (MNEs) and other actors in specific locations, the diversity or heterogeneity of firms matters, as does the diversity of locational environments. The localization of knowledge sources depends on MNE group-level strategies for growth and organizational decentralization, on subsidiary-level evolution towards local competence-creating efforts, and on the development of suitable business networks within locations. MNEs now have a greater potential to benefit from a synergistic locational portfolio of complementary sources of knowledge. The locational composition of the international network for knowledge sourcing of a given MNE depends upon the extent of institutional compatibility between the locations in which the MNE is active. This compatibility between locations in turn affects the capacity of the MNE to become an insider in local business systems, and to influence the local institutional environment.